Impact of partial occlusion of the face on multisensory emotion perception: Comparison of pre- and post-COVID-19 pandemic - Misako Kawahara; Akihiro Tanaka (PLoS ONE, 2025)
We perceive and understand others’ emotional states from multisensory information such as facial expressions and vocal cues. However, such cues are not always available or clear. Can partial loss of visual cues affect multisensory emotion perception? In addition, the COVID-19 pandemic has led to the widespread use of face masks, which can reduce some facial cues used in emotion perception. Thus, can frequent exposure to masked faces affect emotion perception? We conducted an emotion perception task using audio-visual stimuli that partially occluded the speaker’s face. Participants were simultaneously shown a face and voice that expressed either congruent or incongruent emotions and judged whether the person was happy or angry. The stimuli included videos in which the eyes or mouth were partially covered and where the whole face was visible. Our findings showed that, when facial cues were partially occluded, participants relied more on vocal cues for emotion recognition. Moreover, when the mouth was covered, participants relied less on vocal cues after the pandemic compared to before. These findings indicate that partial face masking and prolonged exposure to masked faces can affect multisensory emotion perception. In unimodal emotion perception from only facial cues, accuracy also improved after the pandemic compared to before for faces with the mouth occluded. Therefore, changes in the reliance on vocal cues in multisensory emotion perception during the pandemic period could be explained by improved facial emotion perception from the eye region.